Intrauterine Device Insertion Before and After Mandated Health Care Coverage: The Importance of Baseline Costs. Issue 5 (May 2018) - Heisel, Erica; Kolenic, Giselle E.; Moniz, Michelle M.; Kobernik, Emily K.; Minadeo, Leah; Kamdar, Neil S.; Dalton, Vanessa K.
Abstract : OBJECTIVE: To evaluate changes in out-of-pocket cost for intrauterine device (IUD) placement before and after mandated coverage of contraceptive services and to examine how changes in out-of-pocket cost influence IUD insertion as a function of baseline cost. METHODS: We conducted a cross-sectional pre–post analysis at the plan level using a large deidentified medical claims database to analyze our primary outcome, new IUD insertions among women enrolled in employer-sponsored health plans in 2009 and 2014, and our secondary outcome, out-of-pocket cost. Patient costs and utilization were aggregated by plan and year to conduct a plan-specific analysis. Plans were classified by mean out-of-pocket cost level: no out-of-pocket cost, low out-of-pocket cost (less than the 75th percentile), and high out-of-pocket cost (75th percentile or greater). A generalized estimating equation was used to evaluate average plan utilization of IUD services in 2009 and 2014 as a function of plan cost category and year. RESULTS: Overall, average plan utilization of IUD services demonstrated a significant increase between 2009 (12.5%, 95% CI 11.6–13.4%) and 2014 (13.8%, 95% CI 13.0–14.7%; P <.001). When plans were grouped by out-of-pocket cost level, significant differences in plan utilization over time were observed. Plans that went from high out-of-pocket cost in 2009 to no out-of-pocket cost in 2014 saw a higher average increase in the rate of plan IUD insertions over time (2.4%, 95% CI 0.04–4.5%) compared with plans with no out-of-pocket cost in both 2009 and 2014 (−1.0%, 95% CI −3.3 to 1.4%, P =.02). Among all women in all plans, the 75th percentile of out-of-pocket cost in 2009 was 368; this number dropped to 0 in 2014. CONCLUSION: Women in plans with the greatest reduction in out-of-pocket cost after mandated coverage of contraception had the greatest gains in IUD insertion. This suggests that baseline cost should be considered in evaluations of this policy and others that eliminate patient out-of-pocket cost. Abstract : Women in health plans with the highest out-of-pocket cost before mandated coverage increased their use of intrauterine devices more than any other group.